1956
DOI: 10.2134/agronj1956.00021962004800040010x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Standard Artificial Freezing Technique for Evaluating Cold Resistance of Oats1

Abstract: Synopsis A greenhouse and cold room technique is described which rates cold resistance of oat varieties in the same relative order as that in uniform hardiness experiments in the field. Of various factors influencing survival of seedlings, soil moisture content, temperature, length of cold treatment, and age of seedling had the greatest effect. Hardening treatment, thawing treatment and level of nutrition had small effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1957
1957
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…These results suggest that mass selection was very effective in increasing the frequency of freeze‐tolerant genotypes in the segregating population. Studies have shown that controlled environment freeze resistance is a quantitative trait controlled by genes exhibiting additive effects and the trait had moderate to high heritability (Amirshahi and Patterson, 1956a; Muehlbauer et al, 1970). Our results support these conclusions and provide evidence of the ability of this controlled environment technique to alter gene frequencies rapidly under mass selection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that mass selection was very effective in increasing the frequency of freeze‐tolerant genotypes in the segregating population. Studies have shown that controlled environment freeze resistance is a quantitative trait controlled by genes exhibiting additive effects and the trait had moderate to high heritability (Amirshahi and Patterson, 1956a; Muehlbauer et al, 1970). Our results support these conclusions and provide evidence of the ability of this controlled environment technique to alter gene frequencies rapidly under mass selection.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, progress was slowed by the unpredictable occurrence of winters severe enough to kill tender genotypes and damage those of intermediate hardiness (Marshall, 1992). Early evaluations of oat in controlled environment tests designed to supplement field evaluations used juvenile whole‐plant assays (Murphy et al, 1937; Amirshahi and Patterson, 1956a, 1956b). Subsequent improvements in controlled environment techniques involved evaluation of individual lateral crown meristem tissue from which root and shoot regrowth is regenerated (Marshall, 1965).…”
mentioning
confidence: 99%
“…Although these mortality measurements can be quick and simple, some difficulty can exist in defining what constitutes survival. Estimates of percentage survival are made after periods of recovery varying from 7-10 d (Amirshahi & Patterson, 1956;Pfeifer & Kline, 1960), to 14 d (Arakeri & Schmid, 1949;Pomeroy & Fowler, 1973), 21 d (Fuller & Eagles, 1978) or 42 d (Rogers, Dunn & Nelson, 1977) but even after this length of time plants may be green but subsequently die (Dexter, 1956). It is not uncommon for initial recovery to occur as regrowth but for death to occur later (Anderson & Kiesselbach, 1934).…”
Section: Introductionmentioning
confidence: 99%